Assessment of the clinical course of human rhinovirus/enterovirus infections in pediatric intensive care - Koçoğlu Barlas, Ülkem; Akçay, Nihal; Menentoğlu, Mehmet Emin; Şevketoğlu, Esra; Duyu, Muhterem; Telhan, Leyla; Kanğın, Murat; Tuğrul, Hazal Ceren; Erdoğan, Seher; Durak, Cansu; Güney Şahin, Ebru; Umur, Özge; et al. (Lippincott Williams and Wilkins, 2023)
Background: This study aims to evaluate the clinical course of human rhinovirus/enterovirus (HRV/EV) infections in the pediatric intensive care unit. Methods: The study was conducted as a multicenter, prospective observational study from September 2022 to December 2022. Cases with positive polymerase chain reaction testing for HRV/EV of nasopharyngeal swab samples within the first 24 hours of pediatric intensive care unit admission were recorded. There were 2 groups: 1-24 months and >24 months. Results: A total of 75 cases (39 male) were included in the study. The median age for all cases was 21 months. The highest polymerase chain reaction positivity rates were observed in October (37.33%). Among the cases, 32 (42.67%) presented with bronchopneumonia/pneumonia, 24 (32%) presented with acute bronchiolitis/bronchitis and 7 (9.33%) presented with sepsis/septic shock. The frequency of pediatric acute respiratory distress syndrome was found to be 6.67%. In the age group of 1-24 months, mean lymphocyte and liver enzyme levels were higher, while in the age group of >24 months, mean hemoglobin and mean kidney function test levels were higher (P ? 0.05). Continuous oxygen therapy was provided to 65.3% of the cases, noninvasive ventilation to 33.3%, high-flow nasal cannula-oxygen therapy to 32% and invasive mechanical ventilation to 16%. Conclusions: HRV/EV infections primarily affect the respiratory system and generally exhibit a clinical course with low mortality rates (1, 1.3%). In cases with underlying chronic diseases, more severe clinical conditions such as pediatric acute respiratory distress syndrome and septic shock may occur.
Keywords: Enterovirus; Intensive Care; Pediatric; Rhinovirus; Ventilation